Kultur produzieren künstlerische Praktiken und kritische kulturelle Produktion - Zobl, Elke 1975-; Klaus, Elisabeth 1955-; Moser, Anita; Baumgartinger, Persson Perry 1976-; Bleuler, Marcel 1980-; Drüeke, Ricarda 1976-; Frketić, Vlatka; Smodics, Elke (Edition Kulturwissenschaft, 2019)
The volume collects key concepts in the context of intervening and participatory artistic practices and provides insight into theoretical perspectives and artistic-cultural implementations